Smart Grid Power System by Integrating IOT - et. al., R. Vanitha , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In a typical smart grid, the central management centre controls all the units connected to it making sure to operate them at the highest efficiencies. The central management centre does not only assist in better energy management inside the facility but also it helps in reducing the electrical consumption during peak times. This reduction is reflected as huge energy savings. Our model includes a renewable energy generating block installed in the house or industries which delivers power to batteries and also powers the grid. The power from the generating station is also coupled with the grid. The combined grid can lower the electricity bill and consumption. The renewable energy in our case is from the sun, so hereby we use PV cells to harness the DC power and use power electronics to convert the DC to suitable DC and AC. The converted AC can be connected to the grid. The major including in our smart grid is the implementation of monitoring and control with the help of microcontrollers which can measure the generating voltage and current levels. The monitored values are stored and displayed via cloud to customers by implementing IOT and the state’s power station which helps in more efficient usage of energy and thereby reducing the electricity bill.